If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-2)(x+1)=20
We move all terms to the left:
2(x-2)(x+1)-(20)=0
We multiply parentheses ..
2(+x^2+x-2x-2)-20=0
We multiply parentheses
2x^2+2x-4x-4-20=0
We add all the numbers together, and all the variables
2x^2-2x-24=0
a = 2; b = -2; c = -24;
Δ = b2-4ac
Δ = -22-4·2·(-24)
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{196}=14$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-14}{2*2}=\frac{-12}{4} =-3 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+14}{2*2}=\frac{16}{4} =4 $
| 9-3(2x-4)=4(-3x+7)-2x | | 3k-8=1k= | | -2.75(s+-10)+-11.8=4.52 | | -6x=-5(x-1)+3x | | 17vv+27v+39=180 | | `8-0.25x=0.5x+2` | | 4-2c=-2c+4 | | 3y+4-y=14. | | −7/4v=−83/2 | | t+75=20 | | 4÷n+1=5 | | 68-9c=9c-4 | | 24/y=48 | | 4+3(2x+4)=-2-3x | | 2+5+b=9 | | 9-3(2x-4)=4(-3x7)-2x | | 8j=10−5(9j+2) | | 1/4x+2=15 | | -111=3(5x=3) | | 8=6+2qq= | | -9(x-7)=108 | | 3x+x-5=4x-2-3 | | –12=2+5v+2v | | 5p-9=-9+5p | | -3y+5.8=10 | | y/(-26)=23 | | –x+1=2 | | 4c-2c+1c+10=70 | | v/2+2=9 | | 1/2=49^x-57^x-9 | | 5-2x+x-4+3x=-3 | | 1/3m=11 |